Interventional Therapies for Acute Pulmonary Embolism: Current Status and Principles for the Development of Novel Evidence. Issue 20 (12th November 2019) - Giri, Jay; Sista, Akhilesh K.; Weinberg, Ido; Kearon, Clive; Kumbhani, Dharam J.; Desai, Nimesh D.; Piazza, Gregory; Gladwin, Mark T.; Chatterjee, Saurav; Kobayashi, Taisei; Kabrhel, Christopher; Barnes, Geoffrey D.
Abstract : Pulmonary embolism (PE) represents the third leading cause of cardiovascular mortality. The technological landscape for management of acute intermediate- and high-risk PE is rapidly evolving. Two interventional devices using pharmacomechanical means to recanalize the pulmonary arteries have recently been cleared by the US Food and Drug Administration for marketing, and several others are in various stages of development. The purpose of this document is to clarify the current state of endovascular interventional therapy for acute PE and to provide considerations for evidence development for new devices that will define which patients with PE would derive the greatest net benefit from their use in various clinical settings. First, definitions and limitations of commonly used risk stratification tools for PE are reviewed. An adjudication of risks and benefits of available interventional therapies for PE follows. Next, considerations for optimal future evidence development in this field are presented in the context of the current US regulatory framework. Finally, the document concludes with a discussion of the pros and cons of the rapidly expanding PE response team model of care delivery.